Stereotactic Neurosurgical Treatment Options for Craniopharyngioma - Trippel, Michael; Nikkhah, Guido (Frontiers in Endocrinology, 2012)
Craniopharyngioma are the most common non glial tumors in childhood. The results of different studies indicate that radical excision surgery is not an appropriate treatment strategy for childhood craniopharyngioma with hypothalamic involvement. Stereotactic neurosurgery provides save, minimal invasive and cost efficient options in the treatment of childhood craniopharyngioma. In this review a summary of the contribution of the stereotactic neurosurgery in the interdisciplinary treatment regime of childhood craniopharyngioma will be given and discussed in detail.